2018
DOI: 10.1177/2156759x18823690
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors’ Attitudes Toward Evidence-Based Practices

Abstract: The use of evidence-based practices (EBPs) is growing among school counselors. However, little is known about school counselors' attitudes toward EBPs and related factors. We investigated the relationships between school counselors' grade level, years of experience, theoretical orientation, and attitude toward EBPs. Results indicated that the use of cognitive/behavioral theory and number of years of practice related to attitudes toward EBPs. We offer implications for school counseling practice and future resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Further, the use of EBP is called for in the ASCA Ethical Standards for School Counselors (2016) and in the Council for Accreditation of Counseling and Related Educational Programs' (CACREP, 2016) Standards. Encouragingly, recent research (Mullen, Stevens, & Chae, 2019) suggests that school counselors are open to implementing EBP in school counseling.…”
Section: Evidence-based School Counseling: a Brief Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the use of EBP is called for in the ASCA Ethical Standards for School Counselors (2016) and in the Council for Accreditation of Counseling and Related Educational Programs' (CACREP, 2016) Standards. Encouragingly, recent research (Mullen, Stevens, & Chae, 2019) suggests that school counselors are open to implementing EBP in school counseling.…”
Section: Evidence-based School Counseling: a Brief Reviewmentioning
confidence: 99%
“…For many years, school counseling researchers bemoaned the lack of outcome research about school counseling interventions and programs Whiston & Sexton, 1998), but today, interventions with evidence of efficacy are in every domain of school counseling work, and several national organizations identify relevant resources and disseminate information on their websites (see Appendix for these resources). An ongoing challenge is getting the information to practitioners and counselor educators so that they can use what is now known about effective school counseling practice (Mullen et al, 2019).…”
Section: Evidence-based School Counseling: a Brief Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One key way that the EBSC construct is narrowed is when the student outcomes under consideration are limited. Mullen et al (2019) recently suggested that the ultimate purpose of EBSC is to "select effective services that will enhance students' educational outcomes" (p. 1). If educational outcomes encompass all that contributes to educational and life success, then we agree.…”
Section: Challenges and Opportunities For Ebscmentioning
confidence: 99%
“…Excitingly, our profession is actively grappling with the implications of engaging in evidence-based practices (EBP). In the past year, multiple authors (Borders, 2019;Mullen et al, 2019;Parrow et al, 2019) have explored several topics directly related to EBP in school counseling, while other authors (Savitz-Romer et al, 2019;Warren & Mauk, 2020) have written about issues ancillary to EBP such as research practice partnerships in schools and implementation science in school counseling, respectively. This special issue of Professional School Counseling provides insight into the conference proceedings of the Evidence-Based School Counseling Conference (EBSCC; http:// www.ebscc.org) and to creating an opportunity to continue discussions about ways we can ongoingly evolve our conceptualization of evidence-based school counseling EBSC.…”
mentioning
confidence: 99%